γδ T cells in immunotherapies for B-cell malignancies - Rimailho, Léa; Faria, Carla; Domagala, Marcin; Laurent, Camille; Bezombes, Christine; Poupot, Mary (Frontiers in Immunology, 2023)
Despite the advancements in therapy for B cell malignancies and the increase in long–term survival of patients, almost half of them lead to relapse. Combinations of chemotherapy and monoclonal antibodies such as anti-CD20 leads to mixed outcomes. Recent developments in immune cell-based therapies are showing many encouraging results. γδ T cells, with their potential of functional plasticity and their anti-tumoral properties, emerged as good candidates for cancer immunotherapies. The representation and the diversity of γδ T cells in tissues and in the blood, in physiological conditions or in B-cell malignancies such as B cell lymphoma, chronic lymphoblastic leukemia or multiple myeloma, provides the possibility to manipulate them with immunotherapeutic approaches for these patients. In this review, we summarized several strategies based on the activation and tumor-targeting of γδ T cells, optimization of expansion protocols, and development of gene-modified γδ T cells, using combinations of antibodies and therapeutic drugs and adoptive cell therapy with autologous or allogenic γδ T cells following potential genetic modifications.